Arginase: Mechanisms and Clinical Application in Hematologic Malignancy - Du, Zefan; Li, Tianwen; Huang, Junbin; Chen, Yun; Chen, Chun (Frontiers in Oncology, 2022)
Compared to normal tissues and cells, the metabolic patterns of tumor illnesses are more complex, and there are hallmarks of metabolic reprogramming in energy metabolism, lipid metabolism, and amino acid metabolism. When tumor cells are in a state of fast growth, they are susceptible to food shortage, resulting in growth suppression. Using this metabolic sensitivity of tumor cells to construct amino acid consumption therapy does not harm the function of normal cells, which is the focus of metabolic therapy research at the moment. As a non-essential amino acid, arginine is involved in numerous crucial biological processes, including the signaling system, cell proliferation, and material metabolism. Rapidly dividing tumor cells are more likely to be deficient in arginine; hence, utilizing arginase to consume arginine can suppress tumor growth. Due to the absence of arginine succinate synthase, arginine succinate lyase, and ornithine carbamoyl transferase in some blood tumors, arginases may be employed to treat blood tumors. By investigating the mechanism of arginase treatment and the mechanism of drug resistance in greater depth, arginase treatment becomes more successful in hematological cancers and a new anti-cancer agent in clinical practice.